2004
DOI: 10.1164/rccm.200404-474oc
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Active and Passive Smoking on Habitual Snoring

Abstract: The impact of active smoking, passive smoking, and obesity on habitual snoring in the population is mainly unknown. We aimed to study the relationship of habitual snoring with active and passive tobacco smoking in a population-based sample. A total of 15,555 of 21,802 (71%) randomly selected men and women aged 25-54 years from Iceland, Estonia, Denmark, Norway, and Sweden answered a postal questionnaire. Habitual snoring, defined as loud and disturbing snoring at least 3 nights a week, was more prevalent among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
90
1
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 43 publications
8
90
1
8
Order By: Relevance
“…[8][9][10]14 Previous epidemiologic studies have suggested that smoking may be an independent risk factor for habitual snoring, [7][8][9]10,14 and that snoring frequency increases with the number of cigarettes smoked or the duration of exposure to smoking. [15][16][17][18][19][20][21][22] However, most studies compared patients' smoking history with OSAS prevalence or snoring-related diseases, and the relationship between smoking exposure and OSAS severity was not rigorously investigated or fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[8][9][10]14 Previous epidemiologic studies have suggested that smoking may be an independent risk factor for habitual snoring, [7][8][9]10,14 and that snoring frequency increases with the number of cigarettes smoked or the duration of exposure to smoking. [15][16][17][18][19][20][21][22] However, most studies compared patients' smoking history with OSAS prevalence or snoring-related diseases, and the relationship between smoking exposure and OSAS severity was not rigorously investigated or fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] The correlation between smoking and OSAS has not been studied in detail. In particular, the direct infl uence of smoking on OSAS and the correlation between the amount of cigarette smoking and the severity of OSAS have not been adequately demonstrated.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
See 2 more Smart Citations
“…A large population based survey of 15,555 adults examined the risks associated with active and passive smoking (45). Present smoking, past smoking and passive smoking all contributed to risk of snoring, independently of obesity, sex or age.…”
mentioning
confidence: 99%